Association between weight-adjusted waist index and cardiovascular disease: a systematic review and meta-analysis - Pimenta, Kelly; Madondo, Edmore; Mukhopadhyay, Ayesha; Patel, Jay; Muhit, Samuel; Mzayek, Fawaz; Bartelli, Debra; Smeltzer, Matthew; Zhang, Hongmei (Frontiers in Endocrinology, 2025)
BackgroundThe increasing global prevalence of obesity and cardiovascular disease (CVD) represents a pressing public health challenge. Traditional obesity metrics, such as body mass index (BMI) and waist circumference (WC), have limitations in accurately predicting CVD risk. The weight-adjusted waist index (WWI), a novel metric combining WC and body weight, has been proposed as an alternative predictor of central obesity and its associated risks. This systematic review and meta-analysis aimed to evaluate the association between WWI and CVD.MethodsWe conducted a systematic review of the literature in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, and the study was registered with PROSPERO (ID CRD42024629861), searching PubMed, Scopus, and Google Scholar for observational studies examining the relationship between WWI and CVD. Data extraction and quality assessment were performed independently by two reviewers. A random-effects meta-analysis and subgroup analyzes were conducted to pool effect sizes, expressed as adjusted odds ratios (aORs) or adjusted hazard ratios (aHRs), and heterogeneity was evaluated using I², T², and Q statistics.ResultsTen studies comprising 170,297 participants were included. The pooled analysis revealed a significant positive association between WWI and increased CVD risk, with a pooled OR of 1.33 (95% CI: 1.17-1.48, p < 0.01). Moderate heterogeneity was observed (I² = 38.0%). Subgroup analyses showed stronger associations in studies conducted in the United States (OR: 1.35; 95% CI: 1.24 – 1.47) compared to China (OR: 1.32; 95% CI: 1.17 – 1.48). No significant differences were found between cross-sectional (OR: 1.33) and cohort studies (OR: 1.37).ConclusionsThis study suggests a potential association between WWI and CVD, supporting its utility as an alternative measure of central obesity compared to traditional metrics. Despite these findings, moderate heterogeneity warrants further investigation into population-specific factors and mechanisms underlying the relationship between WWI and CVD. Future research should validate these findings across diverse populations and explore the clinical applications of WWI in CVD prevention strategies.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024629861.